2020
DOI: 10.1016/j.omto.2020.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Efficacy of EGFR Inhibitors by Topical Treatment of Cutaneous Squamous Cell Carcinoma with miR-634 Ointment

Abstract: For cutaneous squamous cell carcinoma (cSCC), topical treatment is an essential option for patients who are not candidates for, or who refuse, surgery. Epidermal growth factor receptor (EGFR) plays a key role in the development of cSCC, but EGFR tyrosine kinase inhibitors (TKIs), such as gefitinib, have shown only partial clinical benefit in this disease. Thus, there is an unmet need to develop novel strategies for improving the efficacy of TKIs in cSCC. We previously demonstrated that the tumor-suppressive mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(38 citation statements)
references
References 62 publications
(44 reference statements)
2
36
0
Order By: Relevance
“…A Japanese group studied the effectiveness of a topical ointment with microRNA (miRNA) 634 combined with a systemic EGFR inhibitor in vitro and then in vivo on mice. If the findings of this study are confirmed in human studies, this combination therapy may become an alternative for cutaneous SCC ineligible for surgery [ 44 ].…”
Section: Discussionmentioning
confidence: 85%
“…A Japanese group studied the effectiveness of a topical ointment with microRNA (miRNA) 634 combined with a systemic EGFR inhibitor in vitro and then in vivo on mice. If the findings of this study are confirmed in human studies, this combination therapy may become an alternative for cutaneous SCC ineligible for surgery [ 44 ].…”
Section: Discussionmentioning
confidence: 85%
“…Cells (1 × 10 4 cells/well) were plated in 96‐well plates and siRNA was transfected the next day at 10 nmol/L using Lipofectamine RNAiMAX (Thermo Fisher Scientific) according to the manufacturer's instructions. After 3 days, cells were stained with 0.1% crystal violet (CV) as described in previous papers 25,26 . The stained cells were lysed with a 2% SDS solution and the optical density (OD) was measured at 560 nm using a microplate reader.…”
Section: Methodsmentioning
confidence: 99%
“…After 3 days, cells were stained with 0.1% crystal violet (CV) as described in previous papers. 25,26 The stained cells were lysed with a 2% SDS solution and the optical density (OD) was measured at 560 nm using a microplate reader. The OD values of cells relative to the control cells transfected with pooled siRNA for the negative control (siNC) were arbitrarily set to 100% to determine the percentage of viable cells.…”
Section: Construction Of the Sirna Library And Cell Growth Assaymentioning
confidence: 99%
“…There are also convincing examples of topical skin cancer treatment with oligonucleotides that validate the possibility of using miRNAs in treating this type of cancer [43]. Inoue et al demonstrated that using a topical ointment containing miR-634 inhibited in vivo tumor growth without toxicity in two different skin tumor models: a cSCC xenograft mouse model and 7,12-dimethylbenz[a]anthracene (DMBA)/12-O-tetradecanoylphorbol-13-acetate (TPA)-induced papilloma mouse model [44].…”
Section: Local Deliverymentioning
confidence: 97%